Complementary and Integrative Medicine in Pediatric Oncology – Development and Evaluation of a Blended Learning Program - Reis, Daniela; Güthlin, Corina; Engler, Jennifer; Schildmann, Jan; Hilje, Clara Carvalho; Mach, Nicolas; Molleker, Christina; Längler, Alfred (Klinische Pädiatrie, 2022)
Background A blended learning program to promote the consultation expertise of pediatric oncologists (POs) on complementary and integrative medicine (CIM) was developed and completed by POs as part of a training program. A previous study indicated that POs in Germany were in need of information and training on CIM, and that there were no medical training offers on the subject in Germany.Methods Evaluation of e-learning (questionnaires) and practically oriented one-day, face-to-face workshops (questionnaires, simulation patients), the workshops were evaluated with regard to changes in quality of physician-patient interaction and with regard of the participants’ feedback.Results 32 POs signed up for the program and completed the e-learning. 22 POs participated in one of the workshops. POs agreed that they had received professionally relevant content during the e-learning. The questionnaires on physician-patient interaction showed neither clear positive nor negative changes concerning the quality of interaction. The feedback from the participants on the workshop was very positive.Conclusion Following the end of the blended learning program the e-learning was made available again for interested POs. 34 further applications were received for participation in this part of the training program. With around 300 POs in Germany, this shows a high demand for further training offers of this kind as well as a need for further development.
Keywords: Complementary medicine; integrative medicine; pediatric oncology; blended learning program; counseling